Pyrénées, vers un millénaire de présence anglaise - Robert Aymard (Anglophonia)
Pyrenean place names keep alive the memory of almost a thousand years of English presence: from Edward I, an English king who was also Duke of Aquitaine (as well as the grandson of Henry II Plantagenet of Anjou and Eleanor of Aquitaine) to summit conquerors such as Lady Lister, Charles Packe and Lord Henry Russell-Killough in more recent times